Rights-Based Social Policy Analysis: A Study of the PNM Mekaar Program - NURMIATI, Dwi Rahayu; KHARISMA, Dinar Dana (PT Batara Swastika Harati, 2024)
The PNM Mekaar program is designed to address the poverty of underprivileged women through access to microfinance and business training. This study aims to analyze the design of the PNM Mekaar program using a rights-based social policy approach. This research uses a literature study method to identify concepts, theories, and empirical data related to women's economic empowerment. The results of the analysis show that the program is still needs-based without guaranteeing economic rights as part of human rights. A rights-based approach demands active participation, accountability, nondiscrimination, and equality in program design. The main findings reveal that although the program is effective in increasing women's income, it has not fully created sustainable structural change. Implementation based on rights principles can ensure that women are not only beneficiaries but also rights holders who can demand accountability. This study concludes the importance of reform policies to strengthen the inclusiveness and desirability aspects of the program in supporting social development goals and gender equality.